The association between frequency of blood donation and the occurrence of low birthweight, preterm delivery, and stillbirth: a retrospective cohort study. Issue 11 (11th August 2016) - Germain, Marc; Delage, Gilles; Robillard, Pierre; Katz, Louis M.; Grégoire, Yves
Abstract : BACKGROUND: Women who donate blood on a regular basis are at high risk of becoming iron depleted. Iron deficiency anemia has been shown to increase the risk of low birthweight and possibly preterm birth. Therefore, there is a concern that regular blood donation by female donors might adversely impact the well‐being of their offspring. This retrospective cohort study examined the association between blood donation and the occurrence of adverse pregnancy outcomes. STUDY DESIGN AND METHODS: The study sample included 18, 483 female blood donors in their childbearing years (age 18 to 45 years) who delivered during the period 2001 to 2011 in the province of Québec (Canada). The occurrence of low birthweight (<2500 g), preterm delivery (<37 weeks of gestation), and stillbirth was ascertained by linking the donor information with provincial birth and stillbirth registries. RESULTS: There was no association between the frequency of donation in the 2‐year period before pregnancy and adverse pregnancy outcomes; compared to women who did not donate during that period, those who donated three or more donations (mean, 3.9 donations) had a relative risk of 0.83 (95% confidence interval [CI], 0.65‐1.06) for low birthweight, 0.91 (95% CI, 0.75‐1.11) for preterm birth, and 0.62 (95% CI, 0.18‐2.12) for stillbirth. These associations remained unchanged after adjusting for baseline characteristics. CONCLUSION: Women who donate blood on a regular but moderate basis do not appear to be at higher risk of adverse pregnancy outcomes. These findings, while reassuring, will need to be replicated in different settings.